Okara protein extracted by alternating ultrasonic/alkali treatment and its improved physicochemical and functional properties - Lu Tang; Xiaolin Liu; Shiru Bai; Dan Zhao; Xuzhen Guo; Dandan Zhu; Guiying Su; Bei Fan; Bo Wang; Liang Zhang; Fengzhong Wang (Ultrasonics Sonochemistry)
Okara protein (OP) is a potential plant-based protein that is beneficial to human health. In this work, an alternating ultrasonic/alkali treatment method with non-continued cavitation and thermal energy output was used to extract protein (AUA-OP) from okara to enhance the functional properties of OP and improve the stability of OP-based emulsions. The purity of AUA-OP was greater than 80%. Compared with traditional (physical-assisted) alkali treatment, FTIR and SDS-PAGE revealed that AUA-OP retained the chemical structure of the protein, but the number of ultrasound-induced exposure sites increased, with increased fluorescence intensity, surface hydrophobicity, and absolute ζ-potential. After alternating ultrasonic/alkali treatment, the protein particles were looser and smaller. In addition, the water/oil holding capacity, EAI, and ESI of AUA-OP further increased. The viscosity of the AUA-OP-stabilized emulsion was also greater. Finally, a 28-day emulsion storage assay revealed that the AUA-OP-stabilized emulsion was stable with a relatively low droplet size and creaming index, indicating great potential for the development of stable protein-based emulsions.